The immunology of sepsis - van der Poll, Tom; Shankar-Hari, Manu; Wiersinga, W. Joost (Immunity (Cambridge, Mass.), 2021)
Sepsis is defined as a life-threatening organ dysfunction caused by a dysregulated host response to an infection. This recently implemented definition does not capture the heterogeneity or the underlying pathophysiology of the syndrome, which is characterized by concurrent unbalanced hyperinflammation and immune suppression. Here, we review current knowledge of aberrant immune responses during sepsis and recent initiatives to stratify patients with sepsis into subgroups that are more alike from a clinical and/or pathobiological perspective, which could be key for identification of patients who are more likely to benefit from specific immune interventions. Recent advances in the field of sepsis have revealed that subgroups of patients can be identified with distinct phenotypic and pathobiological features. van der Poll and colleagues review these new insights and discuss the main pathophysiological pathways implicated in sepsis.